Non-Conviction Based Asset Forfeiture in Criminal Asset Recovery: A Normative Juridical Study from the Perspective of Restorative Justice - Endik Wahyudi; Shalahudin Serbabagus; Fendi Setyawan; Arief Amrullah (MIMBAR YUSTITIA : Jurnal Hukum dan Hak Asasi Manusia, 2025)
Professionalism in law enforcement plays a role in establishing justice, legal certainty, and public trust. However, law enforcement practices in Indonesia reveal disparities between normative legal provisions and their implementation in society. This study aims to analyze the professionalism of law enforcement officers from the perspective of sociology of law and to examine its implications for the legitimacy of law enforcement institutions. The research employs a socio-legal method by integrating normative analysis with the examination of realities in law enforcement practices. The study applies statutory, conceptual, and sociological approaches to evaluate how professionalism influences the legitimacy of law enforcement. The findings demonstrate that professionalism in law enforcement extends beyond technical competence and procedural compliance. It also encompasses integrity, ethical responsibility, independence, accountability, and sensitivity toward values within society. Weak professionalism among law enforcement officers often results in disproportionate enforcement, discriminatory treatment, abuse of discretion, and inconsistency in applying legal norms. These conditions contribute to declining public trust and weakening institutional legitimacy. From the perspective of sociology of law, legal legitimacy is not derived solely from state authority, but also from public acceptance of how laws are implemented fairly and effectively in practice. This study concludes that strengthening the professionalism of law enforcement officers is an essential prerequisite for creating legitimacy and law enforcement. Improving professionalism should not only focus on legal reform but also on strengthening legal culture, professional ethics, and institutional accountability mechanisms in order to achieve justice and maintain public confidence in the rule of law.